Poezja religijna w kręgu mnichów Zakonu Grobu Bożego w Polsce – Gemmae sacrosanctae crucis Jakuba Pawła Radlińskiego - Milewska-Waźbińska, Barbara (Vox Patrum, 2016)
Jakub Paweł Radliński was a General of the Order of the Holy Sepulchre in Miechow between 1744-1765. In 1755 he published in Krakow a religious book Gemmae Sacrosanctae Crucis Nostri Domini Jesu Christi (Jewels of the Sacred Cross of Our Lord Jesus Christ). It is a collection of nearly 150 Latin epigrams preceded by lemmas. The work consists of two parts. In the first section the author develops themes and symbols (figurae) drawn from Scripture, both from the Old, and from the New Testament. The second part contains predictions (prophetiae) on St. Cross. The poems are related to emblems, which were popular in the first half of the eighteenth century. Radliński’s Latin book is worth reminding because of its religious and literary values.